The Influence of Reduced Graphene Oxide Nanoparticles (rGO NPs) on The Microstructure of Metakaolin Geopolymer. Issue 1 (May 2020) - Irfanita, R; Desa, S S; Fahlefy, M R; Wahyuni, S; Athiyyah, U; Amran,; Setiawan, A; Subaer,
Abstract: Reduced graphene oxide nanoparticles (rGO NPs) is one of the advanced green nano-materials with valuable properties that offer promising novel applications particularly when it is combine with other materials. The main objective of this study was to investigate the influence of rGO addition on the microstructure character of metakaolin based geopolymer. Graphene oxide nanoparticles (GO NPs) was synthesized from graphite by using modified Hummer's method and rGO NPs was produced from GO through thermal calcination at 160°C for 4 hours in an autoclave. Geopolymer paste was produced through alkali activation method of metakaolin and cured at temperature 70°C for 2 hours. rGO NPs was dispersed into geopolymer paste with various concentrations, 0, 3, 6 and 9% relative to the mass of metakaolin. The crystal structure and morphology of rGO NPS and geopolymer-rGO NPs composites were investigated by means of x-ray diffraction (XRD), Fourier Transform Infrared (FTIR), scanning electron microscopy (SEM) and The results indicated that rGO NPs as two-dimensional material were successfully produced and characterized. The addition of rGO NPs was found to form strong bond with geopolymer species and hence improve the microstructure character of geopolymer.